PENGEMBANGAN MATERI KEPERCAYAAN DIRI SISWA - Dini Sustrianingsih; Raja Arlizon; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Problems experienced by students in the implementation of education in schools influenced by factors in and outside himself. One of the problems that hinder the process in learning is the low self-confidence of students. In this regard schools play an important role in improving students' self-confidence. But so far the school has not shown any effort to handle it. Therefore it is necessary to develop a material about Student Self Confidence that is expected to be used by guidance and counseling teachers to be submitted to students. This material is prepared using research and development (R & D) methods. The purpose of this study is 1) The creation of Student Self Confidence material in terms of clarity, systematics, image support, update and completeness of the material and support games / video 2) To know the quality of material produced. This material is validated by the lecturers 1 & 2, teachers Counseling Guidance and 38 students SMA Negeri 4 Pekanbaru. This material is tested to students with allocation time 3 hours lesson (3 x 45 '). The results of this material development show the quality of the material produced is in the category of "Very Good", with a score of 4.35 for all aspects of the assessment.Keywords: Modul Of Guidance and Counseling, Self Confidence.